Antimicrobial activity of Pterogyne nitens Tul., Fabaceae, against opportunistic fungi - Regasini, Luis Octávio [UNESP]; Pivatto, Marcos [UNESP]; Scorzoni, Liliana; Benaducci, Tatiane [UNESP]; Fusco-Almeida, Ana Marisa; Mendes-Giannini, Maria José Soares [UNESP]; Barreiro, Eliezer Jesus; Siva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Sociedade Brasileira de Farmacognosia, 2010)
No contexto de nossas pesquisas por novos agentes antifúngicos obtidos da flora brasileira, oito extratos e doze frações de Pterogyne nitens Tul., Fabaceae, foram submetidos ao ensaio antifúngico pelo método de microdiluição, contra quatro espécies de fungos oportunistas, Candida albicans, Candida krusei, Candida parapsilosis e Cryptococcus neoformans. Este trabalho revelou que os extratos e frações de P. nitens foram mais ativos contra C. krusei e C. parapsilosis quando comparados a C. neoformans, sendo que o crescimento de C. albicans foi moderadamente afetado por todos os extratos e frações. As atividades mais potentes foram observadas para as frações n-butanólica dos galhos (CIM = 15,6 μg/mL) e raízes (CIM = 31,2 μg/mL) contra C. krusei. Adicionalmente, a fração n-butanólica dos galhos foi submetida ao fracionamento cromatográfico, resultando no isolamento de quatro alcaloides guanidínicos, sendo N-1,N-2,N-3-tri-isopentenilguanidina (1), descrito pela primeira vez em espécies da família Fabaceae e nitensidinas A-C (2-4), os quais apresentaram atividade antifúngica moderada contra C. krusei (CIM = 62,5 μg/mL) e C. parapsilosis (CIM = 31,2 μg/mL).

As part of our ongoing research on antifungal agents from Brazilian flora, eight extracts and twelve fractions from Pterogyne nitens Tul., Fabaceae, were screened for antimicrobial activity against four opportunistic fungi species (Candida albicans, Candida krusei, Candida parapsilosis and Cryptococcus neoformans) using a broth microdilution method. The present investigation reveals that P. nitens extracts and fractions were more effective against C. krusei and C. parapsilosis than against C. neoformans. The growth of C. albicans was moderately affected by all tested extracts and fractions. The strongest effects were observed for n-butanol fractions from branches (MIC = 15.6 μg/mL) and roots (MIC = 31.2 μg/mL) against C. krusei. Additionally, the chromatographic fractionation of the n-butanol fraction from branches afforded four guanidine alkaloids; N-1,N-2,N-3-triisopentenylguanidine (1), described for the first time in the Fabaceae family, and nitensidines A-C (2-4), which showed moderate activity towards C. krusei (MIC = 62.5 μg/mL) and C. parapsilosis (MIC = 31.2 μg/mL).
Atividade antimicrobiana de Pterogyne nitens Tul., Fabaceae, contra fungos oportunistas
Keywords: Pterogyne nitens; alcaloides guanidínicos; antifúngico; fungos oportunistas; Candida spp; Cryptococcus neoformans; Pterogyne nitens; guanidine alkaloids; antifungal; opportunistic fungi; Candida spp.; Cryptococcus neoformans